A Ring of Voices: Reflections on The Alchemy of Race and Rights - Horn, Sharon K.; Cordano, Roberta J.; McCafferty, Maureen; Patterson, G.; Babcock, Barbara Allen; Peirce, Michael; Khosla, Dinesh; Romany, Celina; Hing, Bill Ong (Columbia Journal of Gender and Law, 1992)
Instead of presenting a traditional book review, the members of the Journal turned to those people Patricia Williams thanks “for their invaluable conversation, inspiration, friendship, and encouragement” for their reflections on The Alchemy of Race and Rights: Diary of a Law Professor.